Pervasive parallel and distributed computing in a liberal arts college curriculum - Newhall, Tia; Danner, Andrew; Webb, Kevin C. (Journal of parallel and distributed computing, 2017)
We present a model for incorporating parallel and distributed computing (PDC) throughout an undergraduate CS curriculum. Our curriculum is designed to introduce students early to parallel and distributed computing topics and to expose students to these topics repeatedly in the context of a wide variety of CS courses. The key to our approach is the development of a required intermediate-level course that serves as an introduction to computer systems and parallel computing. It serves as a requirement for every CS major and minor and is a prerequisite to upper-level courses that expand on parallel and distributed computing topics in different contexts. With the addition of this new course, we are able to easily make room in upper-level courses to add and expand parallel and distributed computing topics. The goal of our curricular design is to ensure that every graduating CS major has exposure to parallel and distributed computing, with both a breadth and depth of coverage. Our curriculum is particularly designed for the constraints of a small liberal arts college, however, much of its ideas and its design are applicable to any undergraduate CS curriculum. •We describe a CS undergraduate curriculum that incorporates PDC topics throughout.•A new intro sequence course that includes PDC.•PDC expanded or added into 9 upper-level course.•Tailored to a liberal arts college, but applicable broadly.